Design of Manufacturing Processes for the Cold Bulk Forming of Small Metal Components from Metal Strip - Stellin, Tommaso (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2017)
The major objective of the work is to generate a basic understanding of manufacturing small metal component from metal strip, in order to reduce the handling limits in multi-stage microforming processes. The design supported by FE-modelling allows a simultaneous analysis of microforming process and strip deformation, in order to ensure a precise handling system. The selection of appropriate process parameters, together with the adoption of harder and thinner raw material, improves the material flow-control and an increase of the microscopic workpiece volume with a simultaneous achievement of a stable process conforming to mass-productio